Pancreatico-gastric fistula arising from IPMN associated with ductal adenocarcinoma of the pancreas: a case report and a literature review - AbuDalu, M.; Munz, Y.; Ohana, G. (Frontiers in Surgery, 2023)
Introduction An intraductal papillary mucinous neoplasm (IPMN) is a potentially malignant cystic tumor that is characterized by an excessive papillary proliferation of mucin-producing epithelial cells. The IPMN usually exhibits different degrees of dysplasia and is accompanied by cystic dilation of the main pancreatic duct (MPD) or side branch. We report a case of an IPMN that has penetrated the stomach and has differentiated into an adenocarcinoma. Case presentation A 69-year-old female, suffering from chronic pancreatitis of unknown etiology, visited our outpatient clinic with complaints of sudden weight loss, diarrhea, and abdominal pain. She underwent several examinations to evaluate the reasons for her sudden onset of symptoms. A gastroscopy showed an ulcerated lesion covered with mucus. CT and magnetic resonance cholangiopancreatography images revealed that the MPD was dilated to 1.3 cm with a fistula formation between the MPD and the stomach. After a multidisciplinary discussion of this case, a total pancreatectomy was proposed. An en bloc total pancreatectomy with gastric wedge resection including the fistula together with splenectomy was carried out. A Roux-en-Y choledochojejunostomy and gastrojejunostomy were performed. Histology results revealed the association of IPMN with invasive carcinoma. Discussion Many reports on IPMN of the pancreas have been published recently. Fistula formation between IPMN and adjacent organs is possible. Given the CT and endoscopic ultrasonography findings, it shows that in our case a main duct IPMN (MD-IPMN) formed a pancreatico-gastric fistula. We point out that the adherence of invasive cancer cells contributed to the fistula formation between the pancreas and the stomach. Conclusion This case report provides evidence for the possibility of IPMN becoming complicated with pancreatico-gastric fistula. Thus, we suggest that surgical resection should be considered in the case of MD-IPMN because of its high propensity for malignant transformation.